Valoración económica de externalidades ambientales de los árboles urbanos y su efecto en el bienestar de las familias en el distrito de Iquitos – Loreto 2022 - Cobos Tuesta, Ingri Carolina (2023)
The research was carried out in the district of Iquitos with families that have urban trees in their homes, it is a descriptive, analytical, cross-sectional study. The primary information was obtained through a structured interview that allowed the development of a hypothetical market on the goods and services that urban trees provide to families and from this an approximation of the economic value was made according to the contingent valuation method. The population considers that the trees offer them some kind of benefits at home, either through shade, freshness and a decrease in temperature. Therefore, they are against the removal of urban trees, evidencing that they highly value their presence. The population shows that they have a high valuation of the environmental services provided by the presence of trees and considers that their removal or absence would affect their health and that of their families, but a small percentage consider that it would not affect them at all. Regarding the WTP of the population, they show that almost all of them are willing to pay for the conservation of urban trees, of which 81 percent are willing to pay less than 100 soles, 10 percent between 100 to 300 soles, the 7 percent between 300 to 1000 soles; while 2 percent are not willing to make any payment for the environmental services provided by urban trees. With the evidence of the results, the null hypothesis is rejected and the alternate hypothesis is accepted, which affirms that the presence of urban trees does produce environmental services that affect the well-being of families.